수직 치조골 신장술 후 증대된 치조골과 임플란트의 예후 평가 - Uttom Kumar Shet; 국민석(Min-Suk Kook); 정승곤(Seunggon Jung); 오희균(Hee-Kyun Oh) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2011)
Introduction: The purpose of this study was to evaluate the clinical result of vertical alveolar distraction, especially the distracted alveolar bone and installed implants. Materials and Methods: Twenty-one patients who have been received the vertical alveolar distraction and implant installation on 22 areas (3 maxilla and 19 mandible) using intraoral alveolar distraction device were examined. After consolidation period of 3-4 months, distraction devices were removed and 91 implants were installed in the distracted alveolar bone. The distracted bone and implants were evaluated clinically and radiographically. Results: Mean height of distracted alveolar bone was 7.5±3.2 mm (range: 2.5-15.0 mm). Mean follow-up period after completion of the distraction was 3.1 years (range: 1.4-11.5 years). Mean resorption of distracted alveolar bone was 1.6±1.8 mm. The success and survival rates of implants was 95.3% and 100%, respectively.. Conclusion: Results of this study indicate that vertical alveolar distraction procedure is a useful and stable method for alveolar ridge augmentation and implantation. KCI Citation Count: 0